Jabung Village Dairy Farmers: Milk Education Center: Peternak Sapi Perah Desa Jabung: Sentra Wahana Eduwisata Susu - Ifit Novita Sari; Otto Fajarianto; Citra Kurniawan; Tri Candra Wulandari; Ena Marlina (Universitas Lancang Kuning, 2023)
Jabung village has a fairly high number of dairy farmers compared to other livelihoods, such as employees, farmers and laborers. This is a great potential for the village to become a special tourism village on dairy farmer edutourism. Currently, the village government is taking inventory of various potential villages that are developed to become tourist villages. The inventory is carried out in stages in line with the activities of the Regrestrasi Awal Sosial Ekonomi (regrosek) specifically for the economy in 2022. The purpose of this service activity is based on the village government's desire to empower a number of dairy farmers to become learning centers for other farmers outside Jabung Village. Preparation is carried out by fixing various supports for the maintenance of dairy cattle. Starting from feeding to milking. Stimulation in the form of animal feed chopping tools, electric cow milking, and the creation of a website following e-learning about dairy cattle